Opportunities and Challenges of Modernizing The Educational System of The Tahfidz Boarding School Medan City - Hasan Asari; Nurmawati Nurmawati; Muhammad Ruslan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to describe the opportunities and challenges of modernizing the Islamic boarding school education system at the Tahfidz Foundation in Medan City (analytic study at the Tahfidz Syarief Sulaimaniyah Foundation and the Tahfiz Islamic Center Foundation, North Sumatra). The problem raised in this study is: what are the opportunities and challenges of modernizing the Islamic boarding school education system at the Tahfidz Foundation in Medan City (analytic study at the Tahfidz Syarief Sulaimaniyah Foundation and the Tahfiz Islamic Center Foundation, North Sumatra)? This research uses a qualitative approach. Data collection techniques in this study were observation, interviews, and document studies. Furthermore, the data analysis technique in this research involves the stages of data reduction, data presentation, and drawing conclusions or verification. The findings in this research indicate that the opportunities for modernizing the Islamic boarding school education system at the Tahfidz Foundation in Medan City, especially at the Tahfidz Syarief Sulaimaniyah Foundation, are: (1) competition to study abroad (in Turkey); (2) ability to respond to industrial technology. 4.0. The challenges faced by the Tahfidz Syarief Sulaimaniyah Foundation in modernizing its education system are: (1) challenges to producing a generation of scholars; (2) society's paradigm of modernity; and (3) accusations of national issues. Whereas the opportunities for modernizing the Islamic boarding school education system at the Tahfidz Islamic Center Foundation in North Sumatra are: (1) mastery of information and communication technology; (2) acceleration of scientific integration; (3) growing the competitive power of students; (4) community enthusiasm for the development of Islamic boarding schools; (5) maintaining and advancing the existence of Islamic boarding schools; and (6) accelerating the regeneration of future leaders. Meanwhile, the challenges faced by Tahfidz Islamic Center Foundation in North Sumatra in modernizing its education system are: (1) the existence of an instant program outside the Islamic boarding school; (2) the crisis of cadres of scholars; and (3) the availability and readiness of human resources.